Cell pathology in bipolar disorder - Rajkowska, Grazyna (Bipolar disorders, 2002)
Objectives: The objective of this paper is to review findings of morphometric postmortem studies conducted on tissues from subjects with bipolar disorder (BPD) to demonstrate that impairments of cell morphology and resilience may underlie the neurobiology of BPD. Methods: Reports of alterations in number, density and size of neurons and glial cells in BPD are reviewed. Owing to the low number of postmortem studies on cellular pathology in BPD, s of recent symposia are also discussed. Results and Conclusions: In BPD, significant reductions in the volume of several brain regions, as well as region‐ and layer‐specific reductions in the number, density and/or size of neurons and glial cells have been demonstrated. Moreover, the results of recent clinical and preclinical studies investigating the molecular and cellular targets of mood stabilizing and antidepressant medications provide intriguing possibilities that impairments in neuroplasticity and cellular resilience may underlie the neurobiology of BPD. Future studies will likely examine the role of both genetic and environmental factors in the pathogenesis and cellular changes in BPD.